Peran Kemampuan Teknologi dalam Meningkatkan Kinerja Pendidik Sekolah Dasar di Kabupaten Takalar - Andriana Andriana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to explain the role of the use of technology in the world of education, especially for the performance of an elementary school educator. The expertise and skills of a teaching staff or teacher in operating technological systems at this time are very important in facing challenges in the era of the industrial revolution 4.0. However, in reality there are still many teaching staff who still lack knowledge in operating technology. In fact, with the use of technology, someone can provide a more concrete picture when presenting material in the learning process. Therefore, it is necessary to implement applications for increasing skills (up-skilling) or updating skills (reskilling) of human resources in order to form competent and competent people. able to innovate optimally in their field. The method used in this research is the literature method which is based on relevant references and then interpreted using the analytical description method, which starts with collecting data systematically and consistently, which is then analyzed, selected and combined to then draw conclusions. using deductive analysis of general problems and then drawing specific conclusions. Then combined with the direct observation method, the results of observations in several elementary schools in Takalar Regency.